2023
DOI: 10.3390/land12071289
|View full text |Cite
|
Sign up to set email alerts
|

How Informed Design Can Make a Difference: Supporting Insect Pollinators in Cities

Abstract: Pollinators are responsible for the reproduction of many plant and crop species and provide important diversity for food webs and cultural value. Despite the critical ecosystem services provided by pollinators, rapid pollinator declines are occurring in response to anthropogenic activities that cause the loss of suitable habitat. There is an opportunity for urban green space to support pollination ecosystem services locally and across the landscape. However, there is a lack of practical but evidence-based guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…There are numerous studies showing that users prefer diversity and species richness [ 67 , 68 ], which is characteristic of a sustainable flower bed. It also promotes biodiversity and attracts pollinators, which is extremely important in today’s challenging times [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies showing that users prefer diversity and species richness [ 67 , 68 ], which is characteristic of a sustainable flower bed. It also promotes biodiversity and attracts pollinators, which is extremely important in today’s challenging times [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated different techniques, incorporating knowledge of species functional traits, that improve the quality of pollinator habitat while also reducing the risk of harming resident species (Majewska & Altizer, 2019;Schueller et al, 2023;Zaninotto et al, 2023). Knowledge of local pollinator diversity and pollinator requirements may aid in the timing of management practices.…”
Section: Are Current Efforts To Incorporate Pollinator Diversity Into...mentioning
confidence: 99%
“…The rapid advancement of urbanization, evident in the relentless expansion of concrete jungles, poses a significant threat to the delicate balance of ecosystem services. Throughout history, cities have endeavored to cultivate thriving human environments [1], a pursuit aligning with Elkington's [2] vision of full-cost accounting for nature and the imperative of sustainable urban development in the long term. Consequently, it becomes crucial to cultivate connections with nature for all urban dwellers while simultaneously mitigating the adverse effects of urbanization on these essential ecosystem services [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it becomes crucial to cultivate connections with nature for all urban dwellers while simultaneously mitigating the adverse effects of urbanization on these essential ecosystem services [3]. However, research reveals that only a paltry 13% of city residents live close enough to nature to enjoy its well-documented mental health benefits [1]. This stark reality underscores the challenge of reconciling the needs of a burgeoning urban populace with the imperative to maintain a healthy and sustainable built environment.…”
Section: Introductionmentioning
confidence: 99%